IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS FOR SMALL AND MEDIUM MICRO-ENTITIES IN THE PREPARATION OF FINANCIAL STATEMENTS - Darul Fahmi (Sean Institute, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are business activities that can expand employment opportunities and provide broad economic services to the community and can play a role in equalizing and increasing community income, encouraging economic growth, and participating in national development. Financial statements aim to analyze financial performance as a benchmark for providing information about a company's financial position and profit and loss, which is helpful for users of financial statements as economic decision-makers. This research is intended for MSME owners who still need financial reports. This research aims to help and facilitate MSME owners in compiling financial reports based on SAK-EMKM. This research is a research using descriptive qualitative method. Data collection was carried out using observation, interviews, and documentation. Thus, this study shows that in carrying out its operational activities,